Increasing the Brand Awareness of Ambassador School Surabaya through A Website - Aprillia Adella Suyanto (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
Ambassador School is a Christian school established in 2011. This school offers 3 main programs which are Baby Class, Preschool, and Elementary. There are 2 schools that are similar to Ambassador School which are Bethany Christian School and CMC/SMI School because of 3 aspects: the location, price, service. The main problem of Ambassador School is related to low brand awareness, in which there are only a small number of people who know about this school and those who know are not able to explain what Ambassador School really is. The best solution of this problem is by increasing Ambassador School’s brand awareness by highlighting its strengths and uniqueness through a website. As the main concern is to increase brand awareness, a website will be the best solution since it does not only tell what a company sells, but also tells other information in detail that other promotional tools may not be able to do the same. There are 4 highlighted USPs: academics, Christian values, character education, and independence education. Highlighting all of this school’s strengths and uniqueness on a website will enable Ambassador School to not only increase the brand awareness, but also lead them to be seen as a more credible and professional school. Keywords: Brand Awareness, Promotional Tool, Website, Unique Selling Point